Modeling Inflation for Mali - Diouf, Mame Astou (IMF Working Papers; Working Paper ;, 2007)
This paper investigates how consumer price inflation is determined in Mali for 1979-2006 along three macroeconomic explanations: (1) monetarist theories, emphasizing the impact of excess money supply, (2) the structuralist hypothesis, stressing the impact of supply-side constraints, and (3) external theories, describing the effects of foreign transmission mechanisms on a small open economy. The analysis makes use of cointegration techniques and general-to-specific modeling. Average national rainfall, and to a lesser extent deviations from monetary and external sector equilibrium are found to be the main long-run determinants of inflation. The paper offers policy recommendations for controlling inflation in Mali.